EFEKTIFITAS IMPLEMENTASI METODE AJAR SCL MODEL SMALL GROUP DISCUSSION - Gantino, Rilla; Ruswanti, Endang; Taufiqurrahman, Taufiqurrahman (Lembaga Penerbitan Unversitas Esa Unggul, 2020)
This study aims to assess the effectiveness of the application of the SCL method with the Small Group Discussion model. SCL implementation in the Advanced Financial Accounting 1 course, Accounting Theory and Financial Statement Analysis is carried out at the Mercu Buana University Accounting Program, the Accounting Theory course is carried out in the Riau University Accounting Program, GCG courses in the Jakarta State University Accounting Program, Accounting Seminar subject in the Accounting Program at Esa Unggul University Jakarta. Implementation of the SCL method by allocating time between the pre-test before the lecture takes place, providing material by the lecturer through the lecture method, providing examples of material implementation at work, student presentations and discussions and ending with a post test. Researchers also confirmed to students and lecturers regarding the implementation of SCL. Based on the results of the pre-test and post-test that were processed, it was found that the SCL teaching method with SGD proved effective because the Asym.Sig (2-tailed) Pre Test and Post Test values were less than 5%, meaning that there was a difference between the learning outcomes of the PreTest and the post Test. It is concluded that there is an effect of using learning methods on the value of learning outcomes.Â Keywords : SCL Method, Small Group Discussion Model, Effectiveness